2023
DOI: 10.1186/s13102-023-00704-5
|View full text |Cite
|
Sign up to set email alerts
|

Early efficacy of postoperative rehabilitation training for lumbar disc herniation

Abstract: Objective To investigate the early clinical efficacy of rehabilitation training after unilateral biportal endoscopy for lumbar disc herniation and to analyze the prognostic factors. Methods A total of 100 patients with lumbar disc herniation who underwent unilateral biportal endoscopy at The Sixth Affiliated Hospital of Nantong University from January 2019 to January 2021 were retrospectively analyzed. The control group was given a standard home-ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…They concluded that the mechanism of gait improvement might be related to pain. Few studies have evaluated the fear-avoidance mental state and gait analysis of patients with lumbar disc herniation and reported that gait was moderately correlated with the fear-avoidance belief questionnaire [ 61 , 65 – 67 ]. Symptoms such as pain appear after the stimulation, so there is a fear-escape psychology for walking, thereby prolonging the limb support phase and slowing down the pace.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the mechanism of gait improvement might be related to pain. Few studies have evaluated the fear-avoidance mental state and gait analysis of patients with lumbar disc herniation and reported that gait was moderately correlated with the fear-avoidance belief questionnaire [ 61 , 65 – 67 ]. Symptoms such as pain appear after the stimulation, so there is a fear-escape psychology for walking, thereby prolonging the limb support phase and slowing down the pace.…”
Section: Discussionmentioning
confidence: 99%